Drug screening using the sweat of a fingerprint: lateral flow detection of Δ9-tetrahydrocannabinol, cocaine, opiates and amphetamine. Issue 2 (1st October 2018) - Hudson, Mark; Stuchinskaya, Tanya; Ramma, Smita; Patel, Jalpa; Sievers, Claudia; Goetz, Stephan; Hines, Selina; Menzies, Eleanor; Russell, David A
Abstract: Here, we describe the use of a fluorescence based lateral flow competition assay for the screening of four classes of drugs, viz, Δ 9 -tetrahydrocannabinol (THC), cocaine (through the detection of benzoylecgonine, BZE), opiates (through the detection of morphine, MOR) and amphetamine (AMP) present in the sweat of a fingerprint. The Drug Screening Cartridge was specifically developed for fingerprint sample collection and analysis. For this study, the cut-offs were set at: 190, 90, 68 and 80 pg/fingerprint for THC, BZE, MOR and AMP, respectively. Working with three UK coroners, the Drug Screening Cartridge, together with its fluorescence reader, was applied to the detection of drugs in the sweat of a fingerprint from deceased individuals. The study shows that there was sufficient sweat present on the fingertips to enable analysis and that the Drug Screening Cartridge could detect the presence, or absence, of each drug. The presence of the drugs was confirmed using LC–MS-MS analysis of a second fingerprint sample collected simultaneously. Excellent correlation was achieved between the results obtained from the Drug Screening Cartridge and the LC–MS-MS analysis of the fingerprint samples obtained from 75 individuals. The accuracy of the results was: 99% for THC; 95% for BZE; 96% for MOR and 93% for AMP. The results obtained using the Drug Screening Cartridge were also compared to toxicological analysis of blood and urine samples with good correlation. The accuracy of the results between the Drug Screening Cartridge and blood was: 96%, 92%, 88% and 97% for THC, BZE, MOR and AMP, respectively. The comparison with urine showed an accuracy ranging between 86% and 92%. This fingerprint sample method has a collection time of just 5 s and a total analysis time of <10 mins. These results show that the lateral flow Drug Screening Cartridge is an excellent screening test to provide information on drug use from the sweat in a single fingerprint sample.